The Influence of Financial Performance, Company Size, and Capital Structure on Company Value in Coal Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Mochamad Gilang Ramadhan (Patua : Journal of Business Administration and Management, 2026)
This study aims to analyze the effect of Non-Performing Loans (NPL), Operating Costs to Operating Income (BOPO), and the Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in conventional commercial banks. The method used in this study is panel data regression with a quantitative approach. The research sample was determined using a purposive sampling technique and processed using the Eviews 13 application. Simultaneously, NPL, BOPO, and LDR significantly influence ROA. This finding indicates that bank profitability is not influenced by a single factor, but rather by a combination of credit risk, operational efficiency, and liquidity. Therefore, optimal management of these three aspects is crucial in improving banking profitability performance.